ChemInform Abstract: A One‐Pot Copper Catalyzed Biomimetic Route to N‐Heterocyclic Amides from Methyl Ketones via Oxidative C—C Bond Cleavage. Issue 19 (May 2015) - Subramanian, Parthasarathi; Indu, Satrajit; Kaliappan, Krishna P.
Abstract: A direct and efficient one‐pot Cu‐catalyzed biomimetic oxidation of readily available methyl ketones to pharmaceutically important N‐heterocyclic amides is reported.